Ventral Pallidal Projections to Mediodorsal Thalamus and Ventral Tegmental Area Play Distinct Roles in Outcome-Specific Pavlovian-Instrumental Transfer - Leung, Beatrice K. (J Neurosci, 2015)
Outcome-specific Pavlovian-instrumental transfer (PIT) demonstrates the way that reward-related cues influence choice between instrumental actions. The nucleus accumbens shell (NAc-S) contributes critically to this effect, particularly through its output to the rostral medial ventral pallidum (VP-m). Using rats, we investigated in two experiments the role in the PIT effect of the two major outputs of this VP-m region innervated by the NAc-S, the mediodorsal thalamus (MD) and the ventral tegmental area (VTA). First, two retrograde tracers were injected into the MD and VTA to compare the neuronal activity of the two populations of projection neurons in the VP-m during PIT relative to controls. Second, the functional role of the connection between the VP-m and the MD or VTA was assessed using asymmetrical pharmacological manipulations before a PIT test. It was found that, whereas neurons in the VP-m projecting to the MD showed significantly more neuronal activation during PIT than those projecting to the VTA, neuronal activation of these latter neurons correlated with the size of the PIT effect. Disconnection of the two pathways during PIT also revealed different deficits in performance: disrupting the VP-m to MD pathway removed the response biasing effects of reward-related cues, whereas disrupting the VP-m to VTA pathway preserved the response bias but altered the overall rate of responding. The current results therefore suggest that the VP-m exerts distinct effects on the VTA and MD and that these latter structures mediate the motivational and cognitive components of specific PIT, respectively.